Learning C♯ - Liberty, Jesse (O'Reilly, 2002)
Most C# books are written for experienced C++ and Java programmers. If you're a novice programmer, or you have experience in VB6 or other procedural programming languages, and you want to learn C#, until now you've been out of luck. That's why Jesse Liberty, author of the best-selling books Programming C# and Programming ASP.NET , has written an entry-level guide to C#. Written in a warm and friendly manner, this book assumes no prior programming experience, and provides an easy introduction to Microsoft's premier .NET language. Learning C# is a complete introduction to C# and object-oriented programming. Learning C# will help you build a solid foundation in .NET, and show how to apply your skills by using dozens of tested examples. Learning C# introduces Visual Studio .NET, a tool set for building Windows and Web applications. You'll learn about the syntax and structure of the C# language, including operators, classes and interfaces, structs, arrays, and strings. Liberty then demonstrates how to develop various kinds of applications--including those that work with databases--and web services. By the time you've finished Learning C# you'll be ready to move on to a more advanced programming guide that will help you create large-scale web and Windows applications. Whether you have a little object-oriented programming experience or you are new to programming altogether, Learning C# will set you firmly on your way to mastering the essentials of the C# language.